GAMOLAN: INSTRUMEN MUSIK TRADISIONAL LAMPUNG BENTUK, FUNGSI, DAN PERKEMBANGANNYA - , Hasyim Kan, S.Sn. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Gamolan is a traditional musical instrument of Lampung in southern Sumatera, which is believed to have existed there since of Hinduism period. It is a percussion instrument made of bamboo, that has been a long heritage of the local agricultural community. Indeed, West Lampung mountainous area has become a main dwelling place of its indigenous hill-tribes people, who had managed to maintain the survival of their generation. Meanwhile their ancestor is believed to have come from Sekala Brak area, which inherited the widespread old Javanese Hinduism keyed gamelan instrument that implied in gamolan. This research aims to investigate the form, function, and development of gamolan instrument, that conducted in ethnomusicology discipline, supported by historical and anthropological approaches. Investigation has shown that gamolan serves as a means of local cultural expression, peopleâs communication, and personal entertainment as well. Apart from its function as solo instrument to perform tabuhan, gamolan is also played to accompany dance and singing, or incorporated into an ensemble of tala (gongs), gindang (doubleheaded drum), and rujih (a pair cymbals). Meanwhile, the song repertoires consisted of hahiwang, bebandung, pepecuch, and muayak, performed in generic or creative forms of tabuhan. In its development, though gamolan have existed long time before the establishment of modern communication such as radio, television, and highway road, however, period of 1960s is considered as the renaissance of gamolan. Paradoxically, when Sekala Brak area of West Lampung has been touched by the technology of information and transportation, gamolan has gradually turned into a marginality in its cultural map, that are urgently in need of rejuvenating and empowerment actions through a definitive attention and participation of local authority and community concerned.